The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1073/pnas.95.12.6756
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid-based defenses in conifers: cDNA cloning, characterization, and functional expression of wound-inducible ( E )-α-bisabolene synthase from grand fir ( Abies grandis )

Abstract: ABSTRACT(E)-␣-Bisabolene synthase is one of two wound-inducible sesquiterpene synthases of grand fir (Abies grandis), and the olefin product of this cyclization reaction is considered to be the precursor in Abies species of todomatuic acid, juvabione, and related insect juvenile hormone mimics. A cDNA encoding (E)-␣-bisabolene synthase was isolated from a wound-induced grand fir stem library by a PCR-based strategy and was functionally expressed in Escherichia coli and shown to produce (E)-␣-bisabolene as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
11

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(117 citation statements)
references
References 40 publications
2
104
0
11
Order By: Relevance
“…Of these three putative sesqui-TPS, the amino acid sequence of PaTPS-Far has highest similarity with the loblolly pine a-farnesene synthase (81% I, 90% S; Phillips et al, 2003), but surprisingly also has very high sequence similarity with the spruce mono-TPS described above (Table II). PaTPS-Bis is most similar to grand fir E-a-bisabolene synthase (86% I, 91% S; Bohlmann et al, 1998a). The third putative sesqui-TPS, PaTPS-Lon, is most similar with d-selinene synthase from grand fir (62% I, 82% S; Steele et al, 1998a).…”
Section: Results Cdna Cloning Of a Family Of Nine Tps Genes From Norwmentioning
confidence: 94%
See 1 more Smart Citation
“…Of these three putative sesqui-TPS, the amino acid sequence of PaTPS-Far has highest similarity with the loblolly pine a-farnesene synthase (81% I, 90% S; Phillips et al, 2003), but surprisingly also has very high sequence similarity with the spruce mono-TPS described above (Table II). PaTPS-Bis is most similar to grand fir E-a-bisabolene synthase (86% I, 91% S; Bohlmann et al, 1998a). The third putative sesqui-TPS, PaTPS-Lon, is most similar with d-selinene synthase from grand fir (62% I, 82% S; Steele et al, 1998a).…”
Section: Results Cdna Cloning Of a Family Of Nine Tps Genes From Norwmentioning
confidence: 94%
“…These studies showed that a family of TPS genes is central to structural diversity of terpenoid defenses (Stofer Vogel et al, 1996;Bohlmann et al, 1997Bohlmann et al, , 1998aSteele et al, 1998a). Recent work in loblolly pine (Pinus taeda) provided information about stereospecificity of cloned pinene synthases in this species (Phillips et al, 2003).…”
mentioning
confidence: 99%
“…(Oxido)squalene cyclases (C 30 ) from both eukaryotes and prokaryotes are representatives [21ϳ24]. Other than triterpene (C 30 ) cyclases, Croteau and co-workers extensively studied reaction mechanisms of enzymes, such as (Ϫ)-limonene synthase (C 10 ) [25], myrcene synthase (C 10 ) [25] (Ϫ)-pinene synthase (C 10 ) [25], (Ϫ)-camphene synthase (C 10 ) [26], (Ϫ)-beta-phellandrene synthase (C 10 ) [26], terpinolene synthase (C 10 ) [26], delta-selinene synthase (C 15 ) [27], gamma-humulene synthase (C 15 ) [27], bisabolene synthase (C 15 ) [28], and abietadiene synthase (C 20 ) [29], etc., from grand fir (Abies grandis). Croteau et al [30] cloned and characterized a gene encoding taxadiene synthase (C 20 ) that catalyzes the committed step of biosynthesis of taxol, an anticancer drug isolated from yew.…”
Section: Biosynthesis Of Isoprenoidsmentioning
confidence: 99%
“…Fig. 2B) demonstrated only weak similarity (,27% identity) to those not involved in labdanerelated diterpenoid biosynthesis (Dudareva et al, 1996;Wildung and Croteau, 1996;Bohlmann et al, 1998b). Slightly higher similarity (approximately 30% identity) was found with the identified gymnosperm bifunctional class II/I diterpene synthases, which are involved in labdane-related biosynthesis (Stofer Vogel et al, 1996;Schepmann et al, 2001;Martin et al, 2004).…”
Section: Sequence Comparison Suggested a Role In Labdane-related Ditementioning
confidence: 99%
“…OsDTS2 was the reference sequence in all cases. The class I terpene synthases not involved in labdane-related diterpenoid biosynthesis, yet containing 'insertional' elements, are linalool synthase from Clarkia breweri (Dudareva et al, 1996), taxadiene synthase from Taxus brevifolia , and bisabolene synthase from Abies grandis (Bohlmann et al, 1998b). Bifunctional class II/I terpene synthases producing labdane-related diterpenes of normal stereochemistry are those from the gymnosperms A. grandis (Stofer Vogel et al, 1996), Ginkgo biloba (Schepmann et al, 2001), and Picea abies (Martin et al, 2004).…”
Section: Sequence Analysis and Alignmentsmentioning
confidence: 99%